Legal Review of Alluvial Land Conflicts from Seawater Sedimentation in Weru Village, Lamongan Regency - Pranata, Keri; Zainudin, Arif; Widyanti, Yenny Eta; Herlindah; Puspitawati, Dhiana (Faculty of Law, Universitas Pekalongan, 2024)
This research is intended to examine the alluvial land conflicts in Weru Village, Paciran District, Lamongan Regency from a legal perspective. The emergence of the Alluvial Land has given birth to disputes between the community and the Village Government. So far, the community has used the Alluvial Land to meet their needs as fishermen. Meanwhile, the village government claims that the land is an asset. On the other hand, the village government wants to build a breakwater. To support the funding, the village government engages the community by buying and selling on behalf of donations to the Alluvial Land. So that this alliance exists, the community feels disadvantaged because of the unclear alliance. This study uses a normative juridical method strengthened with field data to analyse this case. Based on the legal review of this case, First, the Alluvial Land is state land, which, since the emergence of management, has become the responsibility of the state. However, the community or other legal entities can own such property rights based on the terms and conditions of laws and regulations. Second, the engagement carried out by the Village Government with some communities is considered null and void because one of the elements of the agreement is not fulfilled.